Innovation activities in the service sector across EU states: Similarities or differences? - Decyk, Kamil (Publishing House of Wroclaw University of Economics and Business, 2024)
Until 2005, service sector innovation had been a far less popular area of scholarly interest than studies on the industrial sector, the publication in 2005 of the methodological guidelines known as the Oslo Manual, in which it was noted that in addition to technological advancements in the economy, non-technological innovations might also be pursued in economic practice. Since then, although the popularity and dynamics of dedicated research have successively increased, this field of inquiry has not yet been sufficiently explored. Therefore, the aim of this study was to identify and assess the degree of homogeneity among EU countries in terms of innovation activity in the service sector. The hypothesis adopted for this study stated that there are countries within the EU that can be divided into clusters with respect to service sector innovation activity. Bearing in mind the objective and seeking to verify the hypothesis, this research used a critical review of literature, indicator-oriented analysis as well as quantitative statistical methods, among others, while relying on the most up-to-date data from the Eurostat database on innovation activity (as of 5.07.2022). The objective was accomplished using fifteen indicators which describe the effects of innovation activity, which were classified into four groups: innovation activity, types of implemented innovations, types of product innovation, and types of business process innovation. The research proceeded in three stages: identification of groups (clusters) in the area of the surveyed European countries which demonstrated the homogeneity of analysed indicators using Ward’s agglomerative clustering method; identification of significant differences between the defined groups for each indicator carried out, using Student's t-test; an assessment of the degree of homogeneity in the scope of the surveyed EU countries with respect to innovation activity in the service sector by means of the methods outlined above. On the basis of the conducted investigations and the adopted methodology, it may be concluded, first, that the service sectors of the surveyed EU countries can be divided into three homogeneous groups in terms of innovation activity. Second, the similarity within each group was confirmed by Levene’s test, the results of which demonstrated homogeneity of variance for thirteen out of the fifteen analysed indicators. Thirdly, statistical analysis of the findings made it possible to identify significant differences between the defined groups of countries, with the exception of country clusters I and II with respect to three product innovation indicators, as well as country groups II and III relative to three business process innovation indicators, where no significant differences occurred. The conclusions from the study warrant confirmation of the baseline hypothesis, which assumed that the surveyed EU countries could be divided into clusters in terms of service sector innovation activity. The research and the analyses indicated that a homogeneous division of the surveyed EU countries into individual groups in terms of innovative activities in the service sector might offer a point of departure for further, in-depth analysis of the issues addressed in the study. Some of the compelling directions for future investigations include the determination of homogeneity and differences across the industries of the sector in question, as well as the creation of a ranking of countries in line with the analysed indicators. Approaching the issue in this manner will enable a detailed assessment of the innovation activity in the service sector and its internal structures, as well as provide grounds for validating the cluster division presented in this paper.
Argumenta Oeconomica, 2024, Nr 1 (52), s. 221-239
Keywords: innovation activity; similarities and differences; service sector; European Union countries; cluster analysis